THE LCR OF WIRELESS MACRODIVERSITY SSC RECEIVER IN THE PRESENCE OF GAMMA SHADOWED KAPPA-MU FADING - Stefanović, Časlav; Đošić, Danijel (Bulletin of Natural Sciences Research, 2016)
Wireless mobile macrodiversity (MaD) radio system with switch and stay (SSC) receiver and two microdiversity (MiD) selection combining (SC) branches operating over Gamma shadowed Kappa-Mu (k-µ) multipath fading environment is considered. Novel, one-folded integral expression for average level crossing rate (LCR) of MaD SSC receiver output signal envelope is obtained. Numerical results of the proposed model are presented and discussed in relation to the system model parameters.